(untitled) (IAHS Medical Journal, 2023)
Background: Due to the fear of postoperative pain and complications associated with open Milligan-Morgan (MM) surgery, mildly symptomatic patients often hesitate and delay undergoing surgical treatment for internal haemorrhoids. Laser Hemorrhoidoplasty (LHP) has been gaining popularity recently in the management of hemorrhoid. This study aimed to evaluate the efficacy of the LHP compared with MM surgery in the management of internal haemorrhoids. Materials and methods: This multi-center, open label, randomized controlled trial included 60 patietns with secondand third-degree internal haemorrhoids. The patients were randomized in a 1:1 ratio to receive either LHP (Group I) or conventional MM hemorrhoidectomy (Group II). Primary outcome parameter was postoperative pain assessed by Visual Anlougue Scale (VAS) at 24 hours, 7 days and 30 postoperative days. Results: Both the groups were comparable in terms of the demographic characteristics. The mean operation time was significantly lower in group I than group II (19.13±3.42 vs. 28.67±4.54 minutes, p<0.001). The mean VAS score of pain at 24 hours and 7 days postoperative were significantly lower in group I than in group II (p<0.001 and p<0.004, respectively). At postoperative, 30 days the mean VAS scores were similar in both groups (p=0.722). The mean total days of consumed analgesic were significantly shorter in group I than in group II (7.94±5.79 vs. 11.01±2.96 days, p<0.001). The mean time to return to regular activity was significantly earlier in group I than in group II (8.76±3.58 vs. 13.6±3.47, p<0.001). Postoperative bleeding was less in group I than in group II (6.6% vs. 26.7%). The mean length of hospital stay, rate of complete resolution and need for medical treatment for residual symptom and repeated surgery were similar between two groups. Conclusion: LHP was associated with reduction of postoperative pain, postoperative bleeding, and administered with analgesics. So, if available LHP is preferred to open hemorrhoidectomy. IAHS Medical Journal Vol 5(2), Dec 2022; 15-19